Analysis of Meshing Efficiency of Straigh Bevel Gear based on Integrated Lubrication - Tang Xiaogui; Wang Bin; Li Peihong; Chen Xinbo (Jixie chuandong)
In order to predict the transient meshing efficiency of bevel gear pairs,a theoretical model of friction coefficient is established under boundary lubrication,elastohydrodynamic lubrication and mixed lubrication based on the principle of equivalent gear theory,by simplifying bevel gear into equivalent straigh gear,and by computing oil film-thickness ratio. Considering the impact of transitioning factor of mesh point relative sliding velocity,normal load,and friction coefficient,a computing model of friction power losses for bevel gear is established,the math model of sliding and rolling friction power loss is established with a variable of pressure angle and pitch radius by double integration for a meshing cycle,and the simulation analysis of mesh power losses of bevel gear is carried out based on MATLAB.